2016
DOI: 10.1530/erc-15-0572
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive iodine ablation may not decrease the risk of recurrence in intermediate-risk papillary thyroid carcinoma

Abstract: The use of radioactive iodine (RAI) ablation in patients with intermediate-risk papillary thyroid carcinoma (PTC) who show microscopic extrathyroidal extension (ETE), regional lymph node (LN) metastasis, tumors with aggressive histology, or vascular invasion has been debated due to the lack of data regarding long-term prognosis in this risk group. Therefore, the purpose of this study was to resolve the controversy surrounding the prognostic benefit of RAI ablation, especially in intermediate-risk PTC patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…Unfortunately, this study did not analyze diseasespecific survival (DSS), which might be more valuable than overall survival, because the overall survival might be affected by age and comorbidities. In contrast, other investigations did not show any benefit of RAI therapy, including a recent large-sample report from a single center in which RAI therapy did not reduce the risk of loco-regional recurrence in patients with intermediate-risk PTC, even in patients with aggressive characteristics such as BRAF positivity, multifocality, extrathyroidal extension, and regional lymph node metastases [17].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Unfortunately, this study did not analyze diseasespecific survival (DSS), which might be more valuable than overall survival, because the overall survival might be affected by age and comorbidities. In contrast, other investigations did not show any benefit of RAI therapy, including a recent large-sample report from a single center in which RAI therapy did not reduce the risk of loco-regional recurrence in patients with intermediate-risk PTC, even in patients with aggressive characteristics such as BRAF positivity, multifocality, extrathyroidal extension, and regional lymph node metastases [17].…”
Section: Introductionmentioning
confidence: 81%
“…In a retrospective study, Chow SM et al [20] analyzed the subgroup of 352 patients with microscopic extrathyroidal extension and found that RAI treatment can significantly reduce the risk of recurrence. However, in a single institution retrospective studies from South Korea analyzing data from a cohort of 8297 intermediate-risk PTC patients, RAI treatment was not significantly related to the risk of loco-regional recurrence after adjusting for clinicopathological characteristics [17]. Another study from Korea also indicated that RAI treatment did not decrease recurrence in intermediate-risk patients with…”
Section: Plos Onementioning
confidence: 94%
“…The medical decision process for referral to treatment with RAI should therefore incorporate a careful analysis of the benefits and risks for this therapy, particularly in the case of younger patients. Moreover, increasing reports published recently have demonstrated that RAI could not decrease disease-free survival and disease-specific mortality in PTMC patients, even in the intermediate-risk DTC [ 10 , 11 ]. Thus, we performed this retrospective study to evaluate the function of RAI in PTMC with LLNM (belong to intermediated-risk DTC) and explore the prognostic factors for recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, several studies suggested that RAI did not prevent recurrences in patients with PTMC. In Hye Jeong Kim’s study, we have huge concerns about the selection bias since the RAI (−) group was only 30 cases compared with the RAI (+) group of 450 patients in the subgroup of intermediated risk [ 10 ]. Furthermore, 74% cases in RAI (−) group were TNM stage I while only 47% in RAI (+) group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation